2002
DOI: 10.1016/s0378-4290(02)00008-4
|View full text |Cite
|
Sign up to set email alerts
|

Trend and stability analyses of millet yields treated with fertilizer and crop residues in the Sahel

Abstract: Pearl millet (Penisetum glaucum (L.) R.Br.) is a major food crop grown on impoverished sandy soils in the Sahel. A 9-year long-term study was undertaken in the Sahel to test the hypothesis that integrated use of millet crop residues retained on farm ®elds after harvest and mineral fertilizers results in greater and more sustainable yields and conserve soil fertility better than either the use of residue or fertilizer alone. The four treatments compared were: (1) control (crop residue removed and no fertilizer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 33 publications
9
29
0
1
Order By: Relevance
“…Total P was highest under recommended fertilizer and the high rate of crop residue and levels decreased with decreasing fertilizer and crop residue application rates. This is consistent with other studies that found crop residue did not impact available P with fertilizer application (Yamoah et al 2002;Knewtson et al a Control, reduced and recommended fertilizer rates correspond to 0 kg ha -1 N and 0 kg ha -1 P, 15 kg ha -1 N and 4.4 kg ha -1 P, 30 kg ha -1 N and 13.2 kg ha -1 P respectively applied per year for 16 years as CAN and SSP fertilizer b Low, medium, and high manure rates correspond to 300, 900, and 2700 kg ha -1 manure added per year for 16 years c Means followed by the same letter are not significantly different (p C 0.05) using Tukey test for LSD a Control, reduced and recommended fertilizer rates correspond to 0 kg ha -1 N and 0 kg ha -1 P, 15 kg ha -1 N and 4.4 kg ha -1 P, 30 kg ha -1 N and 13.2 kg ha -1 P respectively applied per year for 16 years as CAN and SSP fertilizer b Low, medium, and high crop residue rates correspond to 300, 900, and 2700 kg ha -1 crop residue added per year for 16 years c Means followed by the same letter are not significantly different (p C 0.05) using Tukey test for LSD 2008). There may be no difference in total P between crop residue application rates at lower fertilizer rates because plants are releasing extracellular phosphatase enzymes to mineralize P in crop residues to meet plant P demand (Reddy et al 2000).…”
Section: Yield Average and Trendssupporting
confidence: 93%
See 1 more Smart Citation
“…Total P was highest under recommended fertilizer and the high rate of crop residue and levels decreased with decreasing fertilizer and crop residue application rates. This is consistent with other studies that found crop residue did not impact available P with fertilizer application (Yamoah et al 2002;Knewtson et al a Control, reduced and recommended fertilizer rates correspond to 0 kg ha -1 N and 0 kg ha -1 P, 15 kg ha -1 N and 4.4 kg ha -1 P, 30 kg ha -1 N and 13.2 kg ha -1 P respectively applied per year for 16 years as CAN and SSP fertilizer b Low, medium, and high manure rates correspond to 300, 900, and 2700 kg ha -1 manure added per year for 16 years c Means followed by the same letter are not significantly different (p C 0.05) using Tukey test for LSD a Control, reduced and recommended fertilizer rates correspond to 0 kg ha -1 N and 0 kg ha -1 P, 15 kg ha -1 N and 4.4 kg ha -1 P, 30 kg ha -1 N and 13.2 kg ha -1 P respectively applied per year for 16 years as CAN and SSP fertilizer b Low, medium, and high crop residue rates correspond to 300, 900, and 2700 kg ha -1 crop residue added per year for 16 years c Means followed by the same letter are not significantly different (p C 0.05) using Tukey test for LSD 2008). There may be no difference in total P between crop residue application rates at lower fertilizer rates because plants are releasing extracellular phosphatase enzymes to mineralize P in crop residues to meet plant P demand (Reddy et al 2000).…”
Section: Yield Average and Trendssupporting
confidence: 93%
“…Unexpectedly, crop residue and manure did not interact with fertilizer application to increase SOC beyond fertilizer alone. Difficulty in sequestering OC with organic inputs has been observed in other SubSaharan African long-term trials and was attributed to rapid mineralization and soil erosion from the arid climate and to continuous cultivation and a lack of OM protection in sandy soils (Yamoah et al 2002;Janssen 2011). Trials that were successful in accumulating OC in West Africa were either (a) higher in clay content, which increased aggregation and protected SOM from decomposition (Feller and Beare 1997;Gentile et al 2013) or (b) used manure rates two to three times higher than the maximum of this study (Nakamura et al 2012).…”
Section: Yield Average and Trendsmentioning
confidence: 83%
“…Eghball & Maranville (1993) found that the mean N influx of maize increased with increasing soil N supply. The increased yield with N application is supported by the findings of others who reported increases in grain yields of cereals with N application (Buah et al, 1998;Khosla et al, 2000;Workayehu, 2000;Yamoah et al, 2002;Aflakpui et al, 2005b;Conley et al, 2005). The effect of N fertilizer application in improving soil fertility status and sustainable crop production is demonstrated in the increased grain yield recorded in this study.…”
Section: Grain Yieldsupporting
confidence: 89%
“…Research has demonstrated the importance of inorganic fertilizer in crop production (Buah et al, 1998;Workayehu, 2000;Yamoah et al, 2002;Aflakpui et al, 2005b;Conley et al, 2005). Response to fertilizer is dependent on amount and distributions of moisture, soil fertility and variety.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the minimum FPUE of 15.2% in acid soil and 23.9% in non-calcareous soil was obtained with P25 treatment (Table 3). Thus the finding of our study is in good agreement with the finding of Yamoah et al, (2002) who reported that fertilizer P use efficiency improved significantly, when integrated (organic and inorganic) source of P was used. Fertilizer P uptake efficiency (FPUPE) FPUPE was significantly influenced by the application of different levels of P. The FPUPE reached its maximum (0.035 in acid soil and 0.064 in non-calcareous soil) value when the soils were amended with 100 kg P ha -1 and it was minimum (0.011 in acid soil and 0.023 in non-calcareous soil) value those were fertilized by no P and 150 kg P ha -1 , respectively (Table 4).…”
Section: Fertilizer P Use Efficiency (Fpue)supporting
confidence: 93%